Nanostructured TiO2 Doped with Nb as a Novel Support for PEMFC. (30th May 2013) - Valenzuela, Edgar; Ramos-Sanchez, Victor; Lambert Arista, Alejandro Adolfo; Savadogo, Oumarou
Abstract : Nowadays, one of the major issues of the PEMFC concerns the durability. Historically, carbon has been used as a catalyst support in PEMFC; nevertheless, under the environmental conditions of the cell, the carbon is oxidized, leaving the catalyst unsupported. In order to increase the stability and durability of the catalyst in the PEMFC, a novel nanostructured metallic oxide support is proposed. In this work, TiO2 was doped with Nb to obtain a material that combines chemical stability, high surface area, and an adequate electronic conductivity in order to be a successful catalyst support candidate for long-term PEMFC applications. The TiO2 -Nb nanostructured catalyst support was physically and electrochemically characterized. According to the results, the TiO2 -Nb offers high surface area and good particle dispersion; also, the electrochemical activity and stability of the support were evaluated under high potential conditions, where the TiO2 -Nb proved to be much more stable than carbon.